Multidisciplinary information retrieval second information Retrieval Facility Conference, IRFC 2011, Vienna, Austria, June 6, 2011. Proceedings - Hanbury, Allan; Rauber, Andreas; Vries, Arjen P. (Lecture Notes in Computer Science, 2011)
This book constitutes the proceedings of the Second Information Retrieval Facility Conference, IRFC 2011, held in Vienna, Austria, in June 2011. The 10 papers presented together with a keynote talk were carefully reviewed and selected from 19 high-quality submissions. IRF conferences wish to bring young researchers into contact with industry at an early stage. The second conference aimed to tackle four complementary research areas: information retrieval, semantic web technologies for IR, natural language processing for IR, and large-scale or distributed computing for the above areas. The papers are organized into topical sections on patents and multilinguality, interactive retrieval support, and IR and the Net.